Avaliação da atividade antifúngica in vitro de micropartículas de diidroxiacetona - Fão, Roger Nery (2018)
Currently, the treatment of onychomycosis is based on three forms of treatments: topical therapy, systemic therapy and topical and systemic therapy. Some factors may interfere in the therapeutic response, such as adherence to treatment, possibility of drug interactions and factors related to the patient's clinical status, epidemiological factors and laboratory evaluation. Also, there are factors related to microorganisms, such as the emergence of antifungal resistance, which warns of the need to develop strategies that can prevent its spread. Thus, the objective of this study was to produce an innovative microparticulate formulation containing dihydroxyacetone (DHA) and to evaluate its effects in vitro against Candida spp. through the evaluation of the CIM and CFM. The DHA microparticle formulation (MpDHA) was prepared by the sprinkling method and, after the preparation, the incorporation of the same into a gel was carried out. Subsequently, the in vitro susceptibility of fungal isolates to MpDHA was verified. The determination of the particle diameter showed through the polydispersion (SPAN), which was 1,299 of MpDHA, where they reached reference values for the method used. The Minimum Inhibitory Concentration (MIC) obtained for free DHA and for MpDHA also showed 1.56 mg / mL. Observing the result of the Minimum Fungicide Concentration (CFM), it can be seen that MpDHA showed a fungicidal effect at concentrations lower than the free drug. However, the in vitro assay of antifungal sensitivity to microparticle gel needs to be improved in its standardization, since conclusive results have not been obtained. According to the results of this study, it was concluded that the DHA-containing microparticles obtained an ideal size, with uniform distribution and regular shape, preserving the antifungal activity and potentiating the fungicidal effect against the microorganisms evaluated.